Discovery of imidazo[1, 5-a]pyridines and -pyrimidines as potent and selective RORc inverse agonists. Issue 15 (1st August 2015) - Fauber, Benjamin P.; Gobbi, Alberto; Robarge, Kirk; Zhou, Aihe; Barnard, Adrian; Cao, Jianhua; Deng, Yuzhong; Eidenschenk, Céline; Everett, Christine; Ganguli, Arunima; Hawkins, Julie; Johnson, Adam R.; et al.
Graphical abstract: Abstract: The nuclear receptor (NR) retinoic acid receptor-related orphan receptor gamma (RORγ, RORc, or NR1F3) is a promising target for the treatment of autoimmune diseases. RORc is a critical regulator in the production of the pro-inflammatory cytokine interleukin-17. We discovered a series of potent and selective imidazo[1, 5- a ]pyridine and -pyrimidine RORc inverse agonists. The most potent compounds displayed >300-fold selectivity for RORc over the other ROR family members, PPARγ, and NRs in our cellular selectivity panel. The favorable potency, selectivity, and physiochemical properties of GNE-0946 (9 ) and GNE-6468 (28 ), in addition to their potent suppression of IL-17 production in human primary cells, support their use as chemical biology tools to further explore the role of RORc in human biology.